Corticosteroids in Bell's Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effects of corticosteroids on the early and late outcome of 42 children (21 boys, 21 girls) with Bell's palsy (acute idiopathic facial nerve paralysis) were evaluated in a prospective randomized study at the University of Istanbul, Turkey.